2011
DOI: 10.1007/s12350-010-9304-5
|View full text |Cite
|
Sign up to set email alerts
|

Wide-beam reconstruction half-time SPECT improves diagnostic certainty and preserves normalcy and accuracy: A quantitative perfusion analysis

Abstract: Quantitative perfusion analysis suggests that adaptive noise control with WBR improves uniformity of myocardium comparing to FBP techniques, and results in improved diagnostic certainty while preserving normalcy and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
(12 reference statements)
0
22
0
1
Order By: Relevance
“…The producers of software implemented this method to reconstruction software packages, some of them as a part of software dedicated to particular gamma cameras (GE Healthcare "Evolution for Cardiac", Siemens "Flash3D", Philips "Astonish", Digirad "nSPEED"), another ones as standalone implementations (UltraSPECT "WBR", Hermes Medical Solutions "Hybrid Recon -Cardiology"). In the present work, as in most communications concerning this topic [6][7][8][9], shortening of acquisition time was used as a method for reduction of counts in projection images. Some authors [10] attained reduction of counts by lowering of activity of administered radiopharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
“…The producers of software implemented this method to reconstruction software packages, some of them as a part of software dedicated to particular gamma cameras (GE Healthcare "Evolution for Cardiac", Siemens "Flash3D", Philips "Astonish", Digirad "nSPEED"), another ones as standalone implementations (UltraSPECT "WBR", Hermes Medical Solutions "Hybrid Recon -Cardiology"). In the present work, as in most communications concerning this topic [6][7][8][9], shortening of acquisition time was used as a method for reduction of counts in projection images. Some authors [10] attained reduction of counts by lowering of activity of administered radiopharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on dose reductions from half-time or quarter-time imaging were mostly derived from and supported by the wide-beam SPECT reconstruction (26)(27)(28) in which conventional rotating cameras are used and images are reconstructed without CT-based AC. In the present study, however, we used a hybrid SPECT/CT system with stationary CZT SPECT detectors, and the images were reconstructed via the iterative maximum-likelihood expectation maximization algorithm with CT-based AC.…”
Section: Discussionmentioning
confidence: 99%
“…17 In another clinical trial it was shown that adaptive noise control with WBR improves uniformity of myocardium compared to FBP techniques, and results in improved diagnostic certainty while preserving normalcy and accuracy. 20 In yet another large multicenter trial using half-time upright SPECT acquisition reconstructed with another version of resolution recovery, it was shown this methodology yielded results similar to conventional full acquisition times without compromising perfusion and function information. In general, it can be concluded from the results of these and other clinical trials that half time acquisitions reconstructed with resolution recovery improve image quality over FBP or standard OSEM and provide perfusion information, which is very similar to FBP.…”
Section: Clinical Trialsmentioning
confidence: 98%